Mammalian histones facilitate antimicrobial synergy by disrupting the bacterial proton gradient and chromosome organization - Tory Doolin (Nature Portfolio, 2020)
Histones have a role in antimicrobial defense. Here, the authors show that the histone H2A and the antimicrobial peptide LL-37 exert synergistic effects by enhancing bacterial membrane pores and enabling H2A entry into the bacterial cytoplasm, where it reorganizes DNA and inhibits transcription.